1994
DOI: 10.1111/j.1442-9993.1994.tb01549.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Eucalyptus marginata (jarrah) seedlings in Mediterranean‐climate forest in response to overstorey, site, seedbed, fertilizer application and grazing

Abstract: The effects of overstorey, site, seedbed, seedling density, application of fertilizer and grazing on mortality of Eucalyptus marginala (jarrah) seedlings were studied experimentally in the northern jarrah forest of Western Australia. Rainfall, soil temperature, soil water deficits, leaf water potentials and photosynthetically active radiation (PAR) were monitored. Seedlings on sites with the overstorey removed experienced significantly higher soil temperatures for 9 months of the year (of up to 6°C), smaller s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…This is consistent with previous research in the NJF that has shown seedling mortality typically occurs from competition with overstorey trees for limited soil moisture (Stoneman et al. ). Thus, soil moisture competition from large overstorey trees represents one of the primary factors regulating stem density in the NJF.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous research in the NJF that has shown seedling mortality typically occurs from competition with overstorey trees for limited soil moisture (Stoneman et al. ). Thus, soil moisture competition from large overstorey trees represents one of the primary factors regulating stem density in the NJF.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests potential for on‐going self‐thinning of E. pauciflora forests decades after fire, which might be exacerbated by overstorey suppression of smaller size classes (Barker ; Stoneman et al. ). Other disturbances, such as drought (in particular, a ‘very long’ rainfall deficit from 1996 to 2010 in south‐east Australia; BOM 2010) could have contributed to seemingly high percentage clump mortalities and top‐killed stems (37%) at Unburned sites, as has been recently recorded for other resprouter forests in southern Australia (Prior et al.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient treatments were designed to increase and decrease the availability of the most commonly limiting macronutrients nitrogen and phosphorus, which are widely considered to influence pasture growth and have been shown to increase Eucalyptus establishment in Australian forests (Stoneman et al 1993).Treatments were as follows: high sugar (HS) application of 1.0 kg m -2 of granulated white sugar, shown to substantially reduce soil nitrate available for plant uptake (Prober et al 2005); low sugar (LS) application of 0.33 kg m -2 ; control (no additions); and di-ammonium phosphate (DAP; (NH 4 ) 2 HPO 4 ) fertiliser addition of 15 g m -2 (35.2 kg ha -1 of P). The first round of nutrient addition/depletion began in autumn (early May 2007, almost 5 months before planting, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Growth responses are primarily to N (Moore and Keraitis 1971;Cromer and Jarvis 1990;Kirschbaum et al 1992), P (Kirschbaum et al 1992), or both in interaction (Halsall et al 1983;Fabião et al 1995); the main effects being increased shoot to root ratio, specific leaf area (SLA) and photosynthetic rate (Stoneman 1994). Improved soil nutrition was also shown to reduce seedling mortality of Eucalyptus incrassata seedlings by about 30% (Stoneman et al 1993). The preferred form of N supply is also important and differs between species, with nitrate (NO 3 -)-N producing a stronger response than ammonium (NH 4 ?…”
Section: Introductionmentioning
confidence: 94%